Challenges of continuation of live liver donor programme during COVID-19 pandemic in Pakistan: outcomes and lessons learned - Azhar Hussain; Bilal Ahmed; Abdul Wahab Dogar; Shams Uddin; Syed Hasnain Abbas; Hala Izzo; Kaleem Ullah; Azam Shoaib; Siraj Ud Din; Muhammad Ameer Hamza; Munaza Zafar; Muhammad Affan Qaiser; et al. (BMJ Open Gastroenterology)
Background COVID-19 pandemic has globally affected healthcare including the transplantation programmes.Materials and methods We retrospectively studied the impact of COVID-19 on live liver donor (LLD) programme at liver transplant centre in Gambat, Pakistan. Standard operative procedures (SOPs) including COVID-19 nasopharyngeal swab PCR, CT scans, personal protective equipment use, 6-feet distancing were developed for LLD and transplant team to mitigate COVID-19 exposure. We compared the complications, healthcare utilisation (hospital stay, readmission) and mortality between two LLD cohorts—before and during COVID-19 pandemic from March 2019 to December 2020.Results During study period 300 LLD surgeries were performed. There was an increase in rate of LLDs from 132 (44%) in pre-COVID to 168 (56%) during COVID-19 era. Average numbers of transplants per month performed during pre-COVID and during COVID-19 era were 10.1 and 14, respectively. No donor has developed COVID-19 infection during hospitalisation. Rate of all LLD complications (32 (21.47%) and 49 (29.16%), p=0.43), uneventful discharges (120/168 (71.4%) and 88/132 (66.6%), p<0.05), mean hospital stay (6±2 days and 5±2 days, p=0.17) and readmission (5 (4%) and 3 (1.8%), p=0.43) were similar during the pre-COVID and COVID-19 era. No donor mortality was observed during study period.Conclusion With the implementation of mindful SOPs, rate of LLD increased without any case of COVID-19 infection. Our SOPs were helpful in continuation of LLD programme in a developing country during COVID-19 pandemic.